2015
DOI: 10.1038/srep10877
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two-step deglycosylation via oxidation by glycoside oxidoreductase and defining their subfamily

Abstract: Herein, we report a two-step deglycosylation mediated by the oxidation of glycoside which is different from traditional glycoside hydrolase (GH) mechanism. Previously, we reported a novel flavin adenine dinucleotide (FAD)-dependent glycoside oxidoreductase (FAD-GO) having deglycosylation activity. Various features of the reaction of FAD-GO such as including mechanism and catalytic residue and substrate specificity were studied. In addition, classification of novel FAD-GO subfamily was attempted. Deglycosylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The final step for C-glycosyl bond cleavage was a ␤-elimination-like reaction to produce daidzein and compound 1. Compound 1 has been reported previously as a spontaneous decomposition product of the ␤-elimination of 3-ketocarbohydrates, such as 3-ketosucrose (25), oxidized ginsenoside compound K (26), and 3-keto-levoglucosan (23), under alkaline conditions. Similar ␤-elimination-like cleavage has been observed in glycoside hydrolase families 4 and 109 (27)(28)(29).…”
Section: Discussionmentioning
confidence: 98%
“…The final step for C-glycosyl bond cleavage was a ␤-elimination-like reaction to produce daidzein and compound 1. Compound 1 has been reported previously as a spontaneous decomposition product of the ␤-elimination of 3-ketocarbohydrates, such as 3-ketosucrose (25), oxidized ginsenoside compound K (26), and 3-keto-levoglucosan (23), under alkaline conditions. Similar ␤-elimination-like cleavage has been observed in glycoside hydrolase families 4 and 109 (27)(28)(29).…”
Section: Discussionmentioning
confidence: 98%
“…strain GIN611 with glycoside deglycosylation activity different from that of common glycosidases (GHs). Later [65] they characterized its homologs in Stenotrophomonas maltophilia, Sphingobacterium multivorum, and Agrobacterium tumefaciens strains, catalyzed the deglycosylation via the same mechanism, and suggested these enzymes as a new GMC oxidoreductase subfamily-FAD-dependent glycoside oxidoreductase (FAD-GO). Interestingly, the authors showed broad glycone and aglycon specificities for these enzymes that makes them very attractive in their industrial applications.…”
Section: Auxiliary Activity Family 3 Enzymesmentioning
confidence: 99%
“…This gives us the opportunity to suggest that Zobellia AA3 enzymes could have the same glycoside oxidase activity, identification of which may be the subject for further research. Due to the broad substrate specificity, putative Zobellia FAD-GOs are of particular interest and can be considered as promising biocatalysts for glycoside deglycosylation in food and pharmaceutical industries [65].…”
Section: Auxiliary Activity Family 3 Enzymesmentioning
confidence: 99%
“…These enzymes have not been studied biochemically in detail, yet various Rhizobium , Agrobacterium , and Stenotrophomonas species (phylum Pseudomonadota) and Deinococcus aerius (phylum Deinococcota) were shown to contain genes that are phylogenetically related to bacterial pox genes. Furthermore, the corresponding gene products were able to oxidize either various glycosides ( 25 ) or glucose ( 6 ). FAD-dependent oxidoreductases from Rhizobium , Agrobacterium , and Stenotrophomonas species oxidized the sugar moieties of a range of different ginsenoides, resulting in their deglycosylation.…”
Section: Discussionmentioning
confidence: 99%